Cushing's Syndrome in a Patient With Rathke's Cleft Cyst and ACTH Cell Hyperplasia Detected by 11C-Methionine PET Imaging—A Case Presentation - Sagan, Karol Piotr; Andrysiak-Mamos, Elzbieta; Sagan, Leszek; Nowacki, Przemysław; Małkowski, Bogdan; Syrenicz, Anhelli (Frontiers in Endocrinology, 2020)
Background: Adrenocorticotropic Hormone (ACTH)-dependent Cushing's Syndrome (CS) is most often caused by a pituitary adenoma. Although rarely, it can also result from pituitary corticotroph cell hyperplasia (CH). Reports on concomitant pituitary lesions including ACTH-producing adenomas and Rathke’s cleft cysts (RCCs) have been published. Positron emission tomography (PET), using 11C-labelled-methionine (MET) as a tracer and co-registered with magnetic resonance imaging (MRI) has been shown to be useful in the diagnosis of pituitary collision lesions, however, its role is still under investigation. In this work we present the case of a patient in whom CS was caused by non-adenomatous CH within the wall of an RCC. Case summary: In 2015 a patient with signs and symptoms of CS was referred to our Department. Biochemical studies repeatedly showed elevated midnight serum cortisol and ACTH levels. Magnetic resonance imaging of the sellar region revealed an RCC and MET-PET/MR showed heterogeneous labelled-methionine metabolism in the vicinity of the cyst’s wall. Transsphenoidal surgery resulted in rapid, complete and lasting relief of symptoms. Histopathological examination demonstrated an RCC and CH. Conclusions: Concomitance of pituitary focal lesions is a rare phenomenon. Methionine-labelled PET/MR may be useful in the diagnosis of collision sellar lesions, including CH. Corticotroph cell hyperplasia can present as mild and fluctuating hypercortisolaemia.